A STUDY ON THE ROLE OF THE RB1 GENE AS A PROGNOSTIC FACTOR IN UNTREATED PATIENTS WITH B-CHRONIC LYMPHOCYTIC LEUKEMIA - Vanya Slavcheva; Svetlana Angelova; Georgi Balatzenko; Tzvetan Lukanov; Pencho Tonchev (Peytchinski Publishing, 2022)
Chronic lymphocytic leukemia (CLL) is one of the most common leukemias in adults. After 2000, the FDA approved drugs for its treatment with mechanisms of action different from those of the then-known cytostatics. This new therapeutic approach, employing targeted therapy, is based on a better understanding of the biology and key pathogenetic mechanisms driving the development and progression of the disease. Deletion of the long arm of chromosome 13 is one of the most frequently described cytogenetic aberrations among CLL patients, the prognostic value of which is still debated, given that part of the tumor suppressor genes are located in this chromosome. Our study aimed to investigate the frequency of deletions affecting the retinoblastoma gene (RB1) and their impact on the time to first treatment (TTFT) in untreated B-CLL patients. The cohort included 40 patients with a confirmed diagnosis of CLL and deletion of the DLEU1 gene. Fluorescence in situ hybridization (FISH) was used to determine cytogenetic aberrations affecting the DLEU1 and Rb1 genes. The difference in time to first treatment in patients with/without deletion in the Rb1 gene was determined based on the log-rank test. In our study, we found a shorter time to initiation of first treatment in patients with a deletion in the Rb1 gene. Future clinical studies, including a more significant number of patients with an isolated deletion in the Rb1 gene, would confirm or reject the importance of the mentioned aberration as a prognostic factor and the necessity of its examination in routine practice.